VARIASI GENETIK Lactobacillus fermentum Beijerink ASAL SAYUR ASIN BERDASARKAN ANALISIS RFLP 16S-23S rDNA ISR, RAPD-PCR DAN ERIC-PCR - Sulistiani Sulistiani; Wibowo Mangunwardoyo; Abinawanto Abinawanto; Endang Sukara; Achmad Dinoto; Andi Salamah (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Molecular analysis of Lactobacillus fermentum isolates is essential to understand their genetic variation in relations to their roles in sayur asin fermentation process. Combination of three molecular techniques which is restriction fragment length polymorphism (RFLP) of 16S23S rDNA intergenic spacer region (ISR), random amplified polymorphic DNA (RAPD-PCR) and an enterobacterial repetitive intergenic consensus (ERIC-PCR) analysis were performed to discriminate 19 representative isolates of L. fermentum isolated from sayur asin. The result showed that L. fermentum strain D11 is distantly related to other isolates based on RFLP using HhaI restriction enzyme and RAPDPCR analyses. In addition, both of RAPD-PCR and ERIC-PCR successfully determined the genetic variation among L. fermentum strains by exhibiting distinct 4-8 bands (800-2080 bp) and 4-10 bands (280-3050 bp), respectively. A dendogram generated from UPGMA cluster analysis of both RAPD-PCR and ERIC-PCR data showed two distinct genotypic groups exist among L. fermentum isolated from sayur asin in Indonesia.